2007
DOI: 10.1074/jbc.m701316200
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Free Cholesterol Loading-induced Apoptosis but Preserved Phospholipid Composition of Peritoneal Macrophages from Mice That Do Not Express Group VIA Phospholipase A2

Abstract: Mouse macrophages undergo ER stress and apoptosis upon free cholesterol loading (FCL). We recently generated iPLA 2 ␤-null mice, and here we demonstrate that iPLA 2 ␤-null macrophages have reduced sensitivity to FCL-induced apoptosis, although they and wild-type (WT) cells exhibit similar increases in the transcriptional regulator CHOP. iPLA 2 ␤-null macrophages are also less sensitive to apoptosis induced by the sarcoplasmic reticulum Ca 2؉ -ATPase inhibitor thapsigargin and the scavenger receptor A ligand fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 102 publications
4
56
1
1
Order By: Relevance
“…Materials-Most materials were obtained from sources specified previously (21)(22)(23)(24). Rainbow molecular mass standards, PVDF membranes, and Triton X-100 were obtained from Bio-Rad.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Materials-Most materials were obtained from sources specified previously (21)(22)(23)(24). Rainbow molecular mass standards, PVDF membranes, and Triton X-100 were obtained from Bio-Rad.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblotting Analyses-Cells were harvested and sonicated (15-30 s at 1-s intervals) in appropriate buffer, and an aliquot (30 g) of lysate protein was analyzed by SDS-PAGE (4 -20% Tris-glycine gel, Invitrogen), transferred onto Immobilon-P polyvinylidene difluoride membranes (Bio-Rad), and processed for immunoblotting analyses as described (21)(22)(23)(24). Targeted proteins and primary antibody concentrations were as follows: iPLA 2 ␤ (1:2000 dilution of T-14 antibody from Santa Cruz Biotechnology, Santa Cruz, CA, sc-14463), caspase-3 (1:1000 dilution of H-277 antibody from Santa Cruz Biotechnology, sc7148), cytochrome c oxidase complex IV (COX IV) (1:1000 dilution of antibody 4844 from Cell Signaling Technology, Beverly, MA), anti-FLAG (1:1000; Sigma, F1804), and antipolyhistidine (1:1000; Sigma, H1029).…”
Section: Methodsmentioning
confidence: 99%
“…Since treatment with 10 μM BEL, which does not inhibit secretory PLA 2 or cPLA 2 α (12), inhibited the S1P analog-induced responses, the analogs may stimulate Ca 2+ -independent PLA 2 , resulting in the release of AA. It is reported that free cholesterol loading, which might be attributable to induction of endoplasmic reticulum stress, released AA and caused apoptosis of mouse macrophages in a β-isoform Ca 2+ -independent PLA 2 -mediated pathway (34). The effective S1P analogs for the release of AA such as DMB-mC11S (GS13), which are lipophilic compounds with larger log P values, may interact with intracellular organelles, resulting in the activation of secretory and Ca 2+ -independent PLA 2 s. Further identification of the molecular target(s) of the effective S1P analogs including the subtypes of secretory and Ca 2+ -independent PLA 2 s remains to be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…In L929 cells, AA is reported to increase ceramide levels via the activation of sphingomyelinase and resulting cell death (35). Ca 2+ -independent PLA 2 (β-isofrom) is reported to participate in endoplasmic reticulum stress-induced apoptosis in insulinoma cells (36) and in macrophages (34). Secretory PLA 2 s play important roles in cell damage under pathological conditions including inflammation and atherogeneis (14,16,20).…”
Section: Possible Role Of Release Of Aa In Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation